INFRARED AND RAMAN SPECTROSCOPY STUDIES OF THE α-β PHASE TRANSITION IN CRISTOBALITE - Swainson I.P.; Dove M.T.; Palmer D.C. (My University, 2003)
Infrared and Raman spectra of cristobalite are presented as a function of temperature through the phase transition. The modes are assigned and the assignments compared to those of earlier workers. The compatibility of modes at the G-point of the a-phase with the X and G-points of the -phase is given. In the transition region of ca. 500–550 K, smooth changes in intensity, frequency and linewidths are seen in many modes, indicative of coexistence of a- and -forms.
Keywords: Cristobalite; Silica; Infrared; Raman; Mode assignment; Phase transition